Transfer of brotizolam, periciazine, and sulpiride in cord blood and breast milk, and alprazolam in breast milk: a case report - Jumpei Saito; Yoshiyuki Tachibana; Yuka Sano Wada; Naho Yakuwa; Hiroyo Kawasaki; Tomo Suzuki; Haruhiko Sago; Akimasa Yamatani; Atsuko Murashima (BMC, 2022)
Abstract Background A high prevalence of mental disorders including depression, anxiety, somatoform, and dissociative disorder is reported during pregnancy, however, information on the transfer of antipsychotics across the placenta and into breast milk is limited. We evaluated brotizolam, periciazine and sulpiride in cord blood, maternal serum, and breast milk, and alprazolam in breast milk. Case presentation A 38-year-old woman with dissociative disorder was treated with brotizolam, propericiazine, and sulpiride during pregnancy and lactation, and alprazolam during lactation. The drug concentration ratios for both cord blood and maternal serum were 33.3 and 61.5% for brotizolam and sulpiride, respectively, and periciazine (metabolite of propericiazine) was not detected in the cord blood. In breast milk, alprazolam (0.9 ng/mL), sulpiride (445.8 ng/mL), and periciazine (0.3 ng/mL) concentrations were noted at 7.5 h after the last dose on postpartum, whereas brotizolam was not detected. The relative infant doses via breast milk were 1.4, 2.7 and 0.02% of the maternal daily dose, respectively. The neonate had no congenital anomalies and did not experience any severe withdrawal symptoms after birth. Conclusion Use of brotizolam, propericiazine, and sulpiride during pregnancy and lactation, and use of alprazolam during lactation were acceptable in this case.